A conceptual paper on the students’ perceptions of the importance of Arabic language for tourism industry in Malaysia - Md Sawari, Siti Salwa (2018)
Communication skill is one of the essential elements in tourism or smokeless industry. Oral and written communication skills are the top skills which are important to the tourist workers at different position level. Good communication skill in other foreign languages during the study will add value to the students' profile. Thus, this research attempts to explore the students’ perceptions on the importance of Arabic language for tourism industry in Malaysia. This research also aims to investigate the significant difference of students’ perceptions on the importance of Arabic language for tourism industry across the university. The data were collected from five public universities in Malaysia which offer Bachelor Degree in tourism. A quantitative approach will be adopted in this study. This paper is expected to provide the current tourism students awareness in learning Arabic language. In conclusion, it is hoped that this paper will give some insights to promote the courses in Arabic Language for university students in order to increase their efficiency level concerning the language.